2017
DOI: 10.1515/ling-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of coronal sibilants and stops on the perception of social meanings in Copenhagen Danish

Abstract: Previous studies have shown that the same sociolinguistic feature can be used as a sociolinguistic resource with different indexical potentials in different linguistic as well as social contexts. In this paper we present the results of a perceptual study of indexical meanings of fronted and palatalized variants of /t/ in combination with fronted /s/ in different registers of Copenhagen Danish. The data consist of responses to male speakers’ use of the two variants of /t/ in two different registers that we labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
2
19
0
1
Order By: Relevance
“…In fact, Hyttel-Sørensen (2011) shows that primary school children sometimes perceive a female speaker of street using [t j ] for /t/ to be a boy. That [t j ] also has indexical value for adolescent Danes in Copenhagen was shown in Lillelund and Pharao (2014) and Pharao and Maegaard (2017), where it was found that [t j ] would lead even male speakers of modern to be rated higher on the scales immigrant and gangster by most listeners. Furthermore, it attenuates the perception of male speakers of modern using [s+] to be perceived as "feminine sounding", suggesting at least an indirect link to masculinity for [t j ].…”
Section: The Variables Studiedmentioning
confidence: 89%
See 3 more Smart Citations
“…In fact, Hyttel-Sørensen (2011) shows that primary school children sometimes perceive a female speaker of street using [t j ] for /t/ to be a boy. That [t j ] also has indexical value for adolescent Danes in Copenhagen was shown in Lillelund and Pharao (2014) and Pharao and Maegaard (2017), where it was found that [t j ] would lead even male speakers of modern to be rated higher on the scales immigrant and gangster by most listeners. Furthermore, it attenuates the perception of male speakers of modern using [s+] to be perceived as "feminine sounding", suggesting at least an indirect link to masculinity for [t j ].…”
Section: The Variables Studiedmentioning
confidence: 89%
“…It is described in Quist 2000 as sounding more "staccato" than modern and was shown in Hansen (2005, 2010) to be closer to patterns found in syllabletimed languages, since the difference in duration between phonologically short and long vowels is neutralized in street by making long vowels as short as short vowels (on average, for details see PHARAO; HANSEN, 2010). The prosody of street was shown to have indexical effects of its own in Pharao et al (2014), Lillelund and Pharao (2014) and Pharao and Maegaard (2017) where it was clearly tied to perceptions of speakers as having a 'foreign' or 'immigrant' background, and was also found to be a particularly salient characteristic of this register in Møller (2009) The concept of the type of speech labeled modern is also well described in Danish sociolinguistics. In a series of speaker evaluation experiments, where modern was represented in the stimulus material, Kristiansen and colleagues have shown that modern is consistently evaluated more positively than "Conservative Copenhagen speech" (and more positively than the local dialect as well) on scales concerning self-assurance, fascination, coolness, and friendliness (for an overview of this research, see KRISTIANSEN, 2009).…”
Section: Associations Of Modern and Street In Previous Evaluation Stumentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, sibilant consonants have been a particularly popular area of study among sociophoneticians interested in gender and sexuality. Studies of voiceless fricatives have drawn connections between femininity and a fronted, high frequency /s/ in multiple languages, including English (e.g., Holmes‐Elliott & Levon, ; Levon, ; Munson, McDonald, DeBoe, & White, ; Stuart‐Smith, ; Zimman, 2015, ), Danish (Pharao & Maegaard, ; Pharao, Maegaard, Møller, & Kristiansen, ), Mandarin (Li, ), and Japanese (Heffernan, ). Some studies have suggested that these patterns are rooted in sex differences in the front part of the vocal tract, where /s/ is produced.…”
Section: Received Wisdom On Gender and The Voicementioning
confidence: 99%